Carbetocin is a Functional Selective Gq Agonist That Does Not Promote Oxytocin Receptor Recycling After Inducing β‐Arrestin‐Independent Internalisation. (25th April 2016) - Passoni, I.; Leonzino, M.; Gigliucci, V.; Chini, B.; Busnelli, M.
Abstract : Carbetocin, a long‐acting oxytocin analogue, has been reported to elicit interesting and peculiar behavioural effects. The present study investigated the molecular pharmacology of carbetocin, aiming to better understand the molecular basis of its action in the brain. Using bioluminescence resonance energy transfer biosensors, we characterised the effects of carbetocin on the three human oxytocin/vasopressin receptors expressed in the nervous system: the oxytocin receptor (OXTR) and the vasopressin V1a (V1aR) and V1b (V1bR) receptors. Our results indicate that (i) carbetocin activates the OXTR but not the V1aR and V1bR at which it may act as an antagonist; (ii) carbetocin selectively activates only the OXTR/Gq pathway displaying a strong functional selectivity; (iii) carbetocin is a partial agonist at the OXTR/Gq coupling; (iv) carbetocin promotes OXTR internalisation via a previously unreported β‐arrestin‐independent pathway; and (v) carbetocin does not induce OXTR recycling to the plasma membrane. Altogether, these molecular pharmacology features identify carbetocin as a substantially different analogue compared to the endogenous oxytocin and, consequently, carbetocin is not expected to mimic oxytocin in the brain. Whether these unique features of carbetocin could be exploited therapeutically remains to be established.